Chemical composition of four essential oils from Eupatorium spp. Biological activities toward Tribolium castaneum (Coleoptera: Tenebrionidae) - Lancelle, Hugo Guillermo Ramon (2009)
Toxic and repellent properties of whole essential oils from four Eupatorium (Asteraceae) species (E. buniifolium Hook. et Arn, E. inulaefolium Kunth, E. arnottii Baker, and E. viscidum Hook. & Arn) were investigated in different concentrations toward Tribolium castaneum Herbst adults. The essential oils were isolated by hydrodistillation techniques from the aerial parts. The analysis was performed by GC-FID and GC-MS methods. Contact toxicity assays showed that all the evaluated essential oils were toxic. Furthermore, in all the cases mortality was dose dependent. The main repellency was observed for the essential oil recovered from E. buniifolium.